Butyrate attenuates sympathetic activation in rats with chronic heart failure by inhibiting microglial inflammation in the paraventricular nucleus - Liu Chang; Yu Hao; Xia Hongyi; Wang Ziwei; Li Bolin; Xue Hongmei; Jin Sheng; Xiao Lin; Wu Yuming; Guo Qi (Acta Biochimica et Biophysica Sinica)
Sympathetic activation is a hallmark of heart failure and the underlying mechanism remains elusive. Butyrate is generated by gut microbiota and influences numerous physiological and pathological processes in the host. The present study aims to investigate whether the intestinal metabolite butyrate reduces sympathetic activation in rats with heart failure (HF) and the underlying mechanisms involved. Sprague-Dawley rats (220‒250 g) are anaesthetized with isoflurane, and the left anterior descending artery is ligated to model HF. Then, the rats are treated with or without butyrate sodium (NaB, a donor of butyrate, 10 g/L in water) for 8 weeks. Blood pressure and renal sympathetic nerve activity (RSNA) are recorded to assess sympathetic outflow. Cardiac function is improved (mean ejection fraction, 22.6%±4.8% vs 38.3%±5.3%; P<0.05), and sympathetic activation is decreased (RSNA, 36.3%±7.9% vs 23.9%±7.6%; P<0.05) in HF rats treated with NaB compared with untreated HF rats. The plasma and cerebrospinal fluid levels of norepinephrine are decreased in HF rats treated with NaB. The infusion of N-methyl-D-aspartic acid (NMDA) into the paraventricular nucleus (PVN) of the hypothalamus of HF model rats increases sympathetic nervous activity by upregulating the NMDA receptor. Microglia polarized to the M2 phenotype and inflammation are markedly attenuated in the PVN of HF model rats after NaB administration. In addition, HF model rats treated with NaB exhibit enhanced intestinal barrier function and increased levels of GPR109A, zona occludens-1 and occludin, but decreased levels of lipopolysaccharide-binding protein and zonulin. In conclusion, butyrate attenuates sympathetic activation and improves cardiac function in rats with HF. The improvements in intestinal barrier function, reductions in microglia-mediated inflammation and decreases in NMDA receptor 1 expression in the PVN are all due to the protective effects of NaB.